Resistance to gastrointestinal parasite infection in Djallonké sheep. (16th January 2017) - Traoré, A.; Notter, D. R.; Soudre, A.; Kaboré, A.; Álvarez, I.; Fernández, I.; Sanou, M.; Shamshuddin, M.; Periasamy, K.; Tamboura, H. H.; Goyache, F.
Abstract : Gastrointestinal parasitism places serious constraints on small ruminant production. The situation has been exacerbated by development of drug resistance in many parasite populations, leading to interest in identification of animals with genetically mediated resistance or tolerance to nematode infections. This study assessed the response to natural infection with gastrointestinal nematodes (GIN) in Djallonké sheep during the rainy season in the Sudan-Guinea Savannah region of Burkina Faso. Haemonchus contortus is the most prevalent GIN at this site and time. Djallonké lambs ( n =434) were sampled from 40 households and evaluated at a common location in southern Burkina Faso. Lambs were dewormed with levamisole at 2 to 6 months of age and returned to infected pastures. Fecal egg counts (FEC), packed cell volumes (PCV), and FAffa Malan CHArt (FAMACHA © ) scores were determined 28 and 35 days after deworming. Lamb mortality was monitored throughout the experiment. Least-squares means for BW increased from 13.8±0.2 kg at 28 days to 14.0±0.2 kg at 35 days ( P <0.01). Simple means and medians for FEC were 615 and 100, respectively, at 28 days and 850 and 175, respectively, at 35 days. The FEC exhibited strong right skewness. Following logarithmic transformation and back-transformation of resulting least-squares means to the original scale, FEC were higher ( P <0.01) for males (208±27) than females (122±10). Least-squares means for PCV decreased ( P <0.001) from 28 (36.3±0.5%) to 35 days (33.7±0.5%), and were higher ( P <0.01) for females (36.0±0.4%) than males (33.9±0.7%). Correlations ( r ) between repeated measurements of BW, FEC, PCV and FAMACHA scores at 28 and 35 days were all positive ( P <0.001). The correlation between FAMACHA scores and PCV was negative at 28 ( r =−0.14) and 35 days ( r =−0.18) ( P <0.001). This study revealed that BW was an easily measured predictor of the ability of the lamb to resist infection with GIN and maintain PCV, and confirmed that FAMACHA scores are useful indicators of differences in FEC. Approximately 40% of female and 30% of male lambs did not show detectable levels of infection (i.e. FEC=0) under field conditions. The great variability that was observed in FEC and PCV suggests potential to use Djallonké sheep in breeding programs to enhance resistance to GIN.